Type IV sacrococcygeal teratoma with intraspinal extension treated surgically through an anterior-posterior-anterior approach: A case report - Mouna Zaghedane; Vladimir Gomola; Jean-louis Lemelle; Anthony Joud (Journal of Pediatric Surgery Case Reports)
Introduction: Sacrococcygeal teratomas with intraspinal involvement are rare. To our knowledge, there is only one reported case specifically of a type-IV sacrococcygeal teratoma with intraspinal extension. Case presentation: A 1-day-old female prenatally diagnosed with a type-IV sacrococcygeal teratoma by ultrasound at 37 weeks of gestation was delivered vaginally without complications at 38 weeks and 1 day. Her weight was 3580 g. Physical examination revealed no visible or palpable tumors and no skin abnormalities. The neurological assessment was normal. The patient voided spontaneously and had a spontaneous bowel movement. Postnatal computed tomography (CT) showed a cystic mass in the pelvis with a maximum diameter of 9 cm, compressing the vagina and uterus, which resulted in hydrocolpos. The mass extended through a widened sacral canal up to the S-1 level. The nature of the connection between the mass and the thecal sac and intradural neural elements was not clear. The serum alpha-fetoprotein (AFP) level was 29,448 ng/ml, which is considered normal for the patient’s age. After a multidisciplinary discussion the decision was made to proceed with a combined surgical resection. In supine position and through a laparotomy, the pelvic component was completely freed from all surrounding structures. The patient was then placed in prone position, and through a sacral laminectomy up to L5 we removed the intra-sacral extension of the cystic mass. The thecal sac remained intact. The last segment of the sacrum and the coccyx were excised. The tumor was removed with en-bloc. Last, she was placed again in supine position for the closure of the abdominal incision. She recovered well from the operation. At 12-months of follow-up her development is appropriate for age, and she has no neurological deficits. Conclusion: A combined anterior-posterior-anterior surgical approach is a suitable strategy for the complete resection of type-IV SCTs that have an intraspinal extension.